Morphometric characterisation and performance evaluation of Bhangor indigenous swamp buffalo population of Tripura - SINGH, KARAN VEER; DAS, RAMENDRA; SODHI, MONIKA; KATARIA, R S (The Indian Journal of Animal Sciences, 2022)
An attempt was made to assess the phenotypic variability and study the management practices of indigenous swamp buffalo 'Bhangor' population from the north-eastern state of Tripura. Bhangor buffalo animals have morphological features and behaviour similar to typical swamp buffalo. A survey was conducted in villages covering entire state, to record the phenotypic information. Adult animals are medium sized with compact body and used for draught and meat purpose. The horn is like sickle shaped (curved) with flat broad base and mostly corrugated, and curved upward to form a circle. Recently, for the first time, we had characterised Bhangor buffalo based on cytogenetic analysis as swamp type showing 2N=48 chromosomes. In present study, we had evaluated the reproductive performance and management practices. The buffalo provide valuable draught power in paddy fields. The indigenous population are important and much needed for the local communities as they are most suitably adapted to their natural habitat. At present only few swamp buffalo population are left in the country, and the germplasm of this population needs to be conserved.